Ultra-high carrier mobility InSb film by rapid thermal annealing on glass substrate - Charith Jayanada Koswaththage; Tatsuya Okada; Takashi Noguchi; Shinichi Taniguchi; Shokichi Yoshitome (AIP Advances, 2016)
InSb films were deposited on both mica and glass substrates using thermal evaporation and subjected to FA or RTA. Crystallinity, composition and electrical properties were investigated. High Hall electron mobility as high as 25,000 cm2/(Vs) was obtained with the capped InSb film by keeping the In:Sb ratio after RTA at 520°C for 30 sec or more without adopting epitaxial growth on glass.